Knitmare on Beech Street : a Knit & Nibble mystery - Ehrhart, Peggy (Ehrhart, Peggy. Knit & Nibble mystery., 2023)
"When Pamela, Bettina, and their friends show up at the Voorhees House to greet its new owner, they're met with a most unwelcome sight: a dead body on the kitchen floor. Tassie Hunt just inherited the old Victorian, which had been occupied by a reclusive widow for many years and had a reputation for being haunted. But Tassie would have been unlikely to be spooked since her career involved debunking such paranormal phenomena. Her demise sets off a new flurry of gossip and ghostly speculation in the New Jersey town, of course-and it's tempting to think spirits were indeed involved considering there's zero evidence so far of foul play. A nosy neighbor reports strange lights and sounds, and a man obsessed with the Victorian era starts photographing the place from the street. But it won't take long before Pamela and Bettina are moving in on a killer . . ."--